Chronic lung disease of the very low birth weight infant – is it preventable? - Ogawa, Yunosuke (The Turkish Journal of Pediatrics, 1998)
In Japan, chronic lung disease (CLD) is defined as an oxygen requirement greater than that obtainable in room air at 28 days of age, with symptoms of persistent respiratory distress and a hazy or emphysematous and fibrous appearance upon chest x-ray. A total of 4964 infants weighing less than 1500 g at birth and born in 1990 were admitted to and cared for at level II and III neonatal care centers in Japan. A total of 4293 infants (86.3%) survived at 28 days after birth. Analyses of infants who developed CLD through their preceding illnesses and chest x-ray findings resulted in the classification of CLD into six types. Types I and II are defined as CLD following the acute stage respiratory distress syndrome (RDS). Type I is the typical case of bronchopulmonary dysplasia (BPD) as described previously, whereas Type II shows atypical radiological findings, namely only diffuse haziness without typical emphysema and fibrosis. Type III has a history of intrauterine inflammation. Chest x-ray shows the typical bubbling and cystic appearance described in the original report of Wilson-Mikity syndrome or neonatal pulmonary emphysema in the very low birth weight infant. Type III also has atypical radiological findings in cases with intrauterine infection. Type IV does not have a history of either intrauterine inflammation or RDS but shows typical emphysematous and fibrous appearance upon chest x-ray. Type V includes those with atypical chest x-ray appearance similar to Type II but without history of RDS and intrauterine inflammation. CLD is a heterogeneous condition which shows different spectra. However, the cardinal event is common to all types - the excessive inflammatory response caused by various insults to the immature airways and alveoli, such as oxygen, barotrauma, infection and so on. The excessive inflammatory response leads to lung tissue damage and the abnormal healing process due to immaturity, (such as vitamin A deficiency and insufficient oxygen radical scavenging system) and results in dysplasia and metaplasia of the respiratory system. The treatment of respiratory distress due to CLD also acts as an insult to the lungs and thus forms a vicious cycle. The different spectra of the disease are most possibly attributed to the difference in the timing and the kind of insults to the lungs. In Type I and II CLD, the insults are given in the first hours of life when the infants with surfactant deficiency receive high concentrations of oxygen for stabilization before the surfactant replacement. In Type III and III’ CLD the insults are most likely given before birth. Excessive and sustained inflammatory response in the lungs with different onset times may result in the development of Types IV and V CLD. The strategy for the prevention of CLD should be different according to the origins and causes. The prevention of Types I and II CLD, or CLD following RDS, should be accomplished by successful prophylactic surfactant replacement therapy. Another procedure may be the application of high frequency oscillatory ventilation (HFOV) in the acute stage of RDS or at the time of stabilization right after birth. Types III and III’ CLD present the most difficult challenge for prevention strategy because the disease process already started before birth. At the moment there are no effective measures for prevention. The strategy for the prevention of Types IV and V CLD may reside in the early detection and treatment of patent ductus arteriosus, sepsis and airway infection including pneumonia.